Assessing the relative ages of admixture in the bovine hybrid zones of Africa and the Near East using X chromosome haplotype mosaicism - Freeman, A.R.; Hoggart, C.J.; Hanotte, Olivier H.; Bradley, D.G. (Oxford University Press, 2006)
Historical hybridization events between the two subspecies of cattle, Bos taurus and B. indicus, have occurred in several regions of the world, while other populations have remained nonadmixed. We typed closely linked X chromosome microsatellites in cattle populations with differing histories of admixture from Africa, Europe, the Near East, and India. Haplotype breakdown will occur as admixed populations age, and longer ancestral haplotypes will remain intact in more recently admixed populations compared to older ones. We genotyped male animals from these populations, obtaining unambiguous haplotypes, and measured levels of linkage disequilibrium (LD) and ancestral mosaicism. Extensive LD, likely to be the result of ongoing admixture, was discovered in hybrid cattle populations from the perimeter of the tsetse zone in West Africa. A Bayesian method to assign microsatellite allele ancestry was used to designate the likely origin of each chromosomal segment and assess the relative ages of admixture in the populations. A gradient of the age of admixture in the African continent emerged, where older admixture has produced more fragmented haplotypes in the south, and longer intact haplotypes, indicating more recent hybridization, feature in the northwest.